ROOTS, STEMS, AND BASES THROUGH AFFIXATION PROCESSES IN THE HIKE SHORT STORY - Ardana, Andiva; Hadi, Imron; Alam, Beny (Sekolah Tinggi Bahasa Asing JIA, 2025)
The aim of this research is to find types of morpheme such as roots, stems, and bases in The Hike short story by T. Albert and to find the formation types of morpheme through affixation processes. This research is used descriptive qualitative method, while the data were collected by close reading and observing the words that contains inflection or derivation in “The Hike” short story by T. Albert. This research used the theory of Katamba for analyze types of morpheme. Based on the result of representative data, the stems found in the short story are 31 and the bases found in the short story are 9. All of the words chosen in this research are words that were easily understood by the readers. The formation types of morpheme can be determined through prefix or suffix attached to the word which its affix contain inflection or derivation.